Cloud atlas. (Economist, 2021)
The article informs on rise in competition among cloud computing firms. It mentions that having customers pay only for the information technology they use, while combining different services as needed, is the whole point of cloud computing. It also mentions that businesses main motive for moving to the cloud was never about cost but scalability.